Analisis User Experience Menggunakan HEART Framework dan Importance Performance Analysis (Studi Pada TikTok Shop) - Salma Luthfiyah Yulvi; Mery Citra Sondari (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
This research aims to describe the experiences of TikTok Shop users using two interrelated methods. This research uses a quantitative approach to measure user experience with TikTok Shop. Primary data was collected through an online questionnaire filled in by 257 respondents. The results of measuring user experience using HEART are measured through five variables, namely happiness, engagement, adoption, retention, task success. Based on these measurements, a criterion value for the level of usefulness is produced for each variable. Of the five variables, four are included in the very high criteria because they get a Level of Usability (LoU) value of >80% and one variable is included in the high criteria. It can be interpreted that the level of usability of TikTok Shop is good and following user preferences. Based on the results of the analysis, it is known that using the second method, namely performance importance analysis, that two variables required further feature development, namely happiness and engagement. Indicators that TikTok Shop needs to pay further attention to are simplicity and intensity. The TikTok Shop development team needs to pay attention to the statement of items in quadrant II because they need to continuously remember that they have a good level of importance and performance